Functional hypothalamic amenorrhea in adolescent athletes impairs bone accrual and increases fracture risk - Wong, Laurel; Leibner, Lily; Vicioso, Camila; Shah, Bina; Ranade, Sheena C. (Frontiers in Endocrinology, 2025)
Functional hypothalamic amenorrhea (FHA) is a reversible neuroendocrine condition prevalent among adolescent female athletes that often results from energy deficiency, reflecting an imbalance between energy intake and expenditure due to factors such as disordered eating, psychological stress, and excessive physical activity. By disrupting hypothalamic-pituitary-ovarian (HPO) axis signaling, FHA in adolescence typically leads to hypoestrogenism and subsequent impairment of bone mineral accrual during a crucial period of skeletal development. This review synthesizes current evidence on the pathophysiology of FHA in relation to bone health, emphasizing the impact of altered estrogen, IGF-1, leptin, and cortisol levels. We further summarize the main risk factors of FHA and examine their effect on reduced bone mineral density (BMD), compromised bone microarchitecture, and increased fracture risk. Studies emphasize the high risk of osteopenia, osteoporosis, and stress fractures in female athletes with FHA. Diagnosis of FHA requires exclusion of organic pathology and a multidisciplinary evaluation of orthopedic, nutritional, endocrinological, psychological, and exercise-related contributors. Evidence-based management prioritizes lifestyle modification, nutritional rehabilitation, and psychological support, with transdermal estrogen therapy as a promising treatment for refractory cases. Ongoing controversies include the limited skeletal benefits of oral contraceptives versus growing evidence for transdermal estrogen, and the paradoxical effects of exercise as both protective and harmful under energy-deficient conditions. Additionally, persistent clinical challenges are highlighted, such as underdiagnosis of menstrual dysfunction and lasting microarchitectural deficits despite weight restoration. Ultimately, early identification and intervention are essential to optimize long-term skeletal and reproductive outcomes for adolescent female athletes affected by FHA.